Construction of All Solid State Bi2MoO6/Bi2WO6@Ti3C2 MXene Heterostructure System and the Mechanism Study of the Z-scheme Photocatalysis - Dongfang Zhang; Junkun Liu; Qiang Liu; Jiaxun Wang; Yang Qu (Materials Research)
In this work, all solid-state Z-scheme Bi2MoO6/Bi2WO6@Ti3C2 MXene photocatalytic system was synthesized by a facile solvothermal method. For comparison, pure Bi2MoO6, Bi2WO6 and Bi2MoO6/Bi2WO6 samples were also synthesized. The structure and properties of the as-prepared catalytic materials were analyzed by X‑ray powder diffraction (XRD), transmission electron microscope (TEM) and high-resolution TEM (HRTEM), ultraviolet‑visible diffuse reflection spectroscopy (UV‑Vis DRS), fluorescence spectroscopy (PL), X-ray photoelectron spectroscopy (XPS), N2 adsorption–desorption measurements and photoelectrochemical tests, which were performed to analyze the phase composition, microstructure, morphology, optical properties, and recombination rate of photogenerated charge of the as-prepared samples. Crystal violet (CV)and p-nitrophenol (4-NP) were used as pollutants to simulate wastewater, and the photocatalytic degradation activity of the catalyst samples was evaluated under visible light. After irradiation for 80 min, the as-made Bi2MoO6 /Bi2WO6@Ti3C2 MXene has the best photocatalytic performance, and the degradation rate constant was 3~4 folds higher than that of pure Bi2MoO6 or Bi2WO6. Based on all the experimental characterizations, the corresponding Z-scheme photocatalytic mechanism of the Bi2MoO6 /Bi2WO6@Ti3C2 MXene system was further studied. The results showed that when introducing 2D Ti3C2 MXene, the light absorption range of the Bi2MoO6/ Bi2WO6 heterojunctions were significantly enhanced, and the separation of photogenerated charges were also improved.